Analisis Tindak Tutur Performatif pada Teks Narasi dalam Buku “Teks Narasi dan Literasi Buku Fiksi-Nonfiksi (Cas dari Cerita dan Buku) Modul 5 Bahasa Indonesia Paket B Setara SMP Kelas IX” - Fadhilah Nur Afifah; Aqrima Imaroh; Majidah Majidah; Najahatul Wafa; Salma Alya Nurzakiah; Asep Purwo Yudi Utomo; Tutik Wijayanti (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research is a pragmatic study that focuses on performative speech acts in the Narrative Text in the Book "Narrative Text and Literacy of Fiction-Nonfiction Books (Cas from Stories and Books) Module 5 Indonesian Language Package B Equivalent Junior High School Class IX". Performative speech is an action that has been completed by the speaker and that by expressing it means that the action is completed at that moment. In performative speech there are actions that lead to commissive, representative, conative and directive actions. The purpose of this study is to describe the performative speech acts in the Narrative Text in the Book "Narrative Text and Literacy of Fiction-Nonfiction Books (Cas from Stories and Books) Module 5 Indonesian Language Package B Equivalent Junior High School Class IX" so that it is expected to add references to pragmatics research, especially in speech act research. This research method is descriptive qualitative research, which is a research method that aims to make a systematic description. The research approach used a theoretical approach. The methodology used is descriptive qualitative, which is researching on natural object conditions where the researcher is the key instrument. Data collection techniques through listening, reading and recording techniques. The results of the discussion found 10 data in the form of performative speech acts in the book "Narrative Text and Literacy of Fiction-Nonfiction Books (Cas from Stories and Books) Module 5 Indonesian Language Package B Equivalent Junior High School Class IX". The benefit of this research is that it can be used as a development and development of Indonesian language, can be used as a reference for students to students through data examples obtained in this article and can be used as a treasure of pragmatics literature that is already available.